THE ADVANTAGES OF SENTINEL LYMPH NODE BIOPSY OVER FUNCTIONAL NECK DISSECTION (A REVIEW OF LITERATURE) - I. S. Romanov; S. V. Shiryaеv; Ya. V. Vishnevskaya (Опухоли головы и шеи)
The paper analyzes the data available in the literature on sentinel lymph node biopsy in patients with oral cancer and shows its advantages over prophylactic neck dissection: less pronounced functional and cosmetic consequences, the possibility of a detailed pathomorphological analysis of removed neck lymph nodes macrospecimens with immunohistochemical studies.